Differentially Expressed mRNAs and Their Long Noncoding RNA Regulatory Network with Helicobacter pylori-Associated Diseases including Atrophic Gastritis and Gastric Cancer. (17th November 2020) - Liu, Songyi; Yin, Honghao; Zheng, Shuwen; Chu, Aining; Li, Yizhi; Xing, Chengzhong; Yuan, Yuan; Gong, Yuehua
Abstract : Background . Helicobacter pylori ( Hp ) infection is the strongest risk factor for gastric cancer (GC). However, the mechanisms of Hp -associated GC remain to be explored. Methods . The gene expression profiling (GSE111762) data were downloaded from the GEO database. Differentially expressed genes (DEGs) between normal samples (NO) and Hp -atrophic gastritis (GA) or Hp -GA and Hp -GC were identified by GEO2R. Gene Ontology and pathway enrichment analysis were performed using the DAVID database. lncRNA-TF-mRNA and ceRNA regulation networks were constructed using Cytoscape. The cross-networks were obtained by overlapping molecules of the above two networks. GSE27411 and GSE116312 datasets were employed for validation. Results . DEGs between NO and Hp -GA are linked to the activity of inward rectifying potassium channels, digestion, etc. DEGs between Hp -GA and Hp -GC were associated with digestion, positive regulation of cell proliferation, etc. According to the lncRNA-TF-mRNA network, 63 lncRNAs, 12 TFs, and 209 mRNAs were involved in Hp -GA while 16 lncRNAs, 11 TFs, and 92 mRNAs were contained in the Hp -GC network. In terms of the ceRNA network, 120 mRNAs, 18 miRNAs, and 27 lncRNAs were shown in Hp -GA while 72 mRNAs, 8 miRNAs, and 1 lncRNA were included in the Hp -GC network. In the cross-network, we found that immune regulation and differentiation regulation were important in the process of NO-GA. Neuroendocrine regulation was mainly related to the process of GA-GC. In the end, we verified that CDX2 plays an important role in the pathological process of NO to Hp -GA. Comparing Hp -GA with Hp -GC, DEGs (FPR1, TFF2, GAST, SST, FUT9, and SHH), TF, and GATA5 were of great significance. Conclusions . We identified the DEGs, and their lncRNA regulatory network of Hp -associated diseases might provide insights into the mechanism between Hp infection and GC. Furthermore, in-depth studies of the molecules might be useful to explore the multistep process of gastric diseases.